Various positions a life of Leonard Cohen - Nadel, Ira 1943- (Pantheon Books, 1996)
Already well known in Canada as a poet and novelist when his first record album appeared in 1967, Leonard Cohen saw his reputation grow to international proportions through the release of eight more albums. Recent sold-out concerts and two tribute albums within the past six years attest to his continually expanding popularity. But Cohen has kept his life private: what we know of him we have learned primarily from his often abstract, always highly charged lyrics. With this biography we are finally able to see and understand the man behind the work. Given access to Cohen's private archive of unpublished letters, journals, notebooks, songs, and other writings, and incorporating interviews with Cohen and his closest friends and colleagues, Ira Nadel gives us a remarkably detailed and insightful portrait of this singular artist. We follow both the physical trajectory of his life: from his Montreal childhood in the 1930s and 1940s to his years spent traveling the world; and the artistic: from his first book of poetry, published at age twenty-two, through the experimental novels in the 1960s and the start of his singing and songwriting career in 1966. We observe Cohen's spiritual journey: the lifelong exploration of his Judaism, the three-decades-long practice of Zen Buddhism, the quest for perfection and order that characterizes all his actions and his art. We learn about his friendships and collaborations with other musicians and singers, his tumultuous relationships with women, his severe bouts of depression, and his use of drugs. And Nadel reintroduces us to Cohen's poetry and songs, plumbing the raw emotion and intensity of feeling in the lyrics for their significance in the context of his life. The product of years of research, Various Positions is a rich and revealing account of one of the most daring, literate, and deeply admired songwriters of our time.